Designing a molecular device for organic solar cell applications based on Vinazene: I-V characterization and efficiency predictions - Mohamad, Mazmira (Elsevier Ltd, 2016)
In this study, we investigated the electronic and transport properties of the Vinazene molecular device using the non-equilibrium Green's function (NEGF) formalism combined to the density functional theory (DFT). Transmission spectrum revealed a high tendency of electrons congregate near to the right gold electrode, resulting in an easy electrons transmission from the right gold electrode to the molecule with bias. Similarly, from the density of states calculations, strong electronic interaction between Vinazene molecule and gold electrodes was observed at the molecular junction. The self consistently obtained I-V characteristics curve demonstrated a continuously increase in current with bias as well. Thus, the achieved sinusoidal conductance curve has proven that the transmission channel of the present Vinazene device possessed a steady opening that led to a stable conducting ability of the device. Our calculated efficiency of the Vinazene single molecule solar device, 0.015%, highlights its promise for organic photovoltaic applications.